Brazilian Public Image of the Nurse: Course of Nurse's Assistência Particular Nossa Senhora da Gloria (1920-1928) - Fernando Porto; Elaine Fonseca; Anna Karine de Mattos Desvelandes; Luciana Luchesi Barizon; Wellington Mendonça de Amorim (Universidad de Alicante, 2012)
Study with a central focus of analysis in fac- simile posted on the magazine Fon-Fon on the Course of Nursing of Assistencia Nossa Senhora da Gloria. Analysis approach was through the perspective of historical-semiotic. Methodologically, the documents were written and imagery used, the latter being analyzed through a matrix analysis, and historically contextualized. The results showed a further course of Nurses before, probably unknown to researchers in the History of Nursing in Brazil, which increasingly must relativize the studies on this topic since the documentation of collections and many governments must be scrutinized to hit assertive.